Innovation in mental health services: Where are we now? - Subrata, Sumarno Adi; Abdelaal, Heba Mohamed; Abd-Elrazek, Mira Naguib (Universitas Muhammadiyah Magelang, 2024)
The mental health landscape has undergone a profound transformation in recent years, driven Alongside the recognition that innovative approaches are essential to address the growing needs of individuals grappling with mental health challenges. This editorial explores the current state of innovation in mental health services, examining the emerging technologies, models of care, and research advancements that are shaping the future of mental health support. The editorial delves into the potential of artificial intelligence and precision mental health to revolutionize the delivery and personalization of mental health interventions. It also highlights the progress made in technology-based interventions, such as internet-based psychotherapeutic approaches and virtual reality applications, which have demonstrated promising results in treating various psychiatric conditions. Furthermore, the editorial discusses the challenges and opportunities inherent in the integration of these innovative tools and strategies into mental health service delivery. With synthesizing the latest research and insights, this paper aims to provide a comprehensive understanding of the current state of innovation in mental health services and the promising avenues for future development, ultimately empowering clinicians, policymakers, and individuals to navigate the evolving landscape of mental health care. Keywords: Mental health; innovation technology; artificial intelligence; precision mental health; internet-based interventions